Peningkatan Keterampilan Membaca Nyaring Siswa Dengan Penggunaan Media Kartu Kata Mata Pelajaran Bahasa Indonesia Kelas II SDN SUKABUMI 1 - ., Indah Kusumawati; ., Ludfi Arya Wardana; ., Didit Yulian Kasdriyanto (CV. ITTC INDONESIA, 2023)
Learning Indonesian plays a very important role before other learning in the main teaching and learning process. However, there are still many problems that occur in the elementary school environment with low reading skills. This research was conducted because there was a low level of students' reading aloud skills when the Indonesian subject took place in class II students at SDN Sukabumi 1, Probolinggo City. This problem is due to the lack of educator skills in utilizing learning media. With this, researchers are challenged to be able to fix these problems by applying word card media. This research was conducted using a Classroom Action Research (CAR), analysis of data acquisition based on the results of tests and interviews and data analysis using descriptive qualitative and descriptive quantitative. There was an increase in the implementation of cycle I and cycle II with an average of 56.14 in cycle I and an increase in cycle II of 82.3 with the complete category.